Screening Iran's Culture : A Narrative Study of Female Managers in Glass Organizations. - Karimi, Nikoo (2010)
The “glass ceiling” is one of the most compelling metaphors for analyzing inequalities between men and women in the workplace. There is considerable evidence that women encounter a glass ceiling or barrier to advancement into the executive ranks of organizations. Although many expected this barrier to be obliterated with the large influx of women entering the work force over the last two decades, little change has actually occurred in the most senior ranks. This research focuses on emerging evidence which indicates that the trend in Iranian corporations is stronger due to many domestic socio-cultural issues which are identified to be provoked from Iran‟s history, traditions and Islam in particular. The purpose of this qualitative study is to understand and discover the experiences, challenges, and barriers women encounter while aspiring, seeking, and serving in senior level leadership positions in the Asian country of Iran. This paper explored Iranian female superintendents‟ perceived barriers through a qualitative approach. The qualitative approach allowed the researcher to obtain narrative information on specific barriers, challenges and experiences of women superintendents. Open-ended response questions allowed participants the opportunity to clarify barriers, challenges and experiences and gave a personal input on how these variables affected or enhanced their careers.